A modified conditioning regimen based on low‐dose cyclophosphamide and fludarabine for haploidentical hematopoietic stem cell transplant in severe aplastic anemia patients at risk of severe cardiotoxicity. Issue 1 (30th October 2021) - Lin, Fan; Zhang, Yuanyuan; Han, Tingting; Cheng, Yifei; Mo, Xiaodong; Wang, Jingzhi; Chen, Yuhong; Wang, Fengrong; Tang, Feifei; Han, Wei; Yan, Chenhua; Xu, Zhengli; et al.
Abstract: Severe cardiotoxicity is a fatal complication during high‐dose cyclophosphamide (Cy)‐based conditioning in hematopoietic stem cell transplant (HSCT) for severe aplastic anemia (SAA). This study aimed to evaluate the feasibility and efficacy of a modified conditioning regimen in haploidentical HSCT (haplo‐HSCT) for severe‐cardiotoxic‐risk SAA patients. This BuCy low Flu conditioning utilized busulfan (Bu, 3.2 mg/kg for 2 days), low‐dose Cy (100 mg/kg), fludarabine (150 mg/m 2 ), and rabbit antithymocyte globulin (rATG, 10 mg/kg). Compared to BuCy conditioning using high‐dose Cy of 200 mg/kg, Bu of 3.2 mg/kg for 2 days, and rATG of 10 mg/kg, the incidence of severe cardiotoxicity of BuCy low Flu conditioning was significantly decreased (2.17% vs 12.80%, p = .032). The engraftment rates (100% for neutrophil and 84.44% for platelet) were favorable. The probabilities of 100‐day transplant‐related mortality were similar in the BuCy low Flu and the BuCy group (8.75% vs 10.53%, p = .671). Both 1‐year overall survival (88.79% vs 84.66%, p = .357) and 1‐year failure‐free survival (84.78% vs 81.70%, p = .535) were comparable. The BuCy low Flu group had higher rates of cytomegalovirus and Epstein–Barr virus reactivation. In conclusion, the BuCy low Flu provided reduced severe cardiotoxicity, and achieved favorable engraftment and survival. Our results suggest BuCy low Flu conditioning can be a feasible alternative for haplo‐HSCT recipients at risk of severe cardiotoxicity.